Revealing the Effect of Work-From-Home on Job Performance during the Covid-19 Crisis: Empirical Evidence from Indonesia - Susilo, Donny (The journal of contemporary issues in business and government, 2020)
This study aims to determine the effect of work-from-home on job performance. It proposes work environment, job satisfaction and work motivation as mediating variables, and answers how work-from-home affects employee performance through them. The study has implications for business practitioner who intend to measure the effectiveness of their work-from-home policies. This is especially pertinent during the coronavirus crisis. The original contribution of this study lies within its questionnaire that has been attuned to changes caused by COVID-19. Data collection was completed by distributing an online questionnaire to workers in Indonesia. The questionnaire with a Likert scale was sent to approximately 2720 employees by email and a link was also shared on social media. The survey attracted 330 respondents. To answer the research questions, this study used structural equation modelling. The output revealed that working from home, employees experienced greater enjoyment, satisfaction and motivation thus enhancing job performance. While the validity of this research is constrained in scope to how these benefits are manifested in Indonesia, there may be external validity among other countries affected by COVID-19.